Design principles of noble metal-free electrocatalysts for hydrogen production in alkaline media: combining theory and experiment. Issue 24 (15th November 2021) - Jung, Hyeonjung; Choung, Seokhyun; Han, Jeong Woo
Abstract : This review discusses the rational design of efficient electrocatalysts by understanding alkaline hydrogen evolution reaction and oxygen evolution reaction mechanisms, as achieved by combining experimental and computational approaches. Abstract : Water electrolysis is a promising solution to convert renewable energy sources to hydrogen as a high-energy-density energy carrier. Although alkaline conditions extend the scope of electrocatalysts beyond precious metal-based materials to earth-abundant materials, the sluggish kinetics of cathodic and anodic reactions (hydrogen and oxygen evolution reactions, respectively) impede the development of practical electrocatalysts that do not use precious metals. This review discusses the rational design of efficient electrocatalysts by exploiting the understanding of alkaline hydrogen evolution reaction and oxygen evolution reaction mechanisms and of the electron structure–activity relationship, as achieved by combining experimental and computational approaches. The enhancement of water splitting not only deals with intrinsic catalytic activity but also includes the aspect of electrical conductivity and stability. Future perspectives to increase the synergy between theory and experiment are also proposed.